The effects of an individual with post-traumatic stress reaction (PTSR) on the total family system: a qualitative investigation - Haarhoff, Dale (University of Limpopo (Medunsa Campus), 2010)
The phenomenon of trauma from violent crime is deeply rooted within the South African community (Human Rights Watch, 2008). Various studies has researched the resulting post-traumatic stress reaction (PTSR) of the trauma victim, with far-reaching implications for an understanding of the emotional, cognitive, physiological, and social level of functioning of the victim (Edwards, 2005). Punctuating from the general systems theory, however, it is clear that the trauma victim does not function in isolation, but forms part of certain circular patterns of interaction within a family system. Change in one part of this system will induce change in the system as a whole (Becvar & Becvar, 2006). The aim of this research project was to move away from exclusively focusing on the trauma victim and to investigate the effects, if any, on the whole family system if one of its members experienced a PTSR. Data was collected from qualitative interviews with a family member of each trauma victim, someone who had not directly experienced the traumatic incident. The data was transcribed verbatim and analysed, in accordance with qualitative methodology by three independent, systemically trained clinicians. The findings indicate that there is a significant effect on the whole family system, and that all the members of this system experience some form of PTSR as a secondary traumatic experience. The ability of the system to cope effectively with this environmental demand is based largely on the effectiveness of its patterns of communication. These findings have important implications for our understanding of the phenomenon of trauma, trauma prevention and intervention strategies.
Thesis (M MSc (Clinical Psychology))--University of Limpopo,2010.
Keywords: Stress disorders, post-traumatic; Stress disorders, post-traumatic